Analisis faktor-faktor yang mepengaruhi muzakki membayar zakat di BAZNAS Yogyakarta - Andi Triyawan (University of Darussalam Gontor, 2016)
The awareness society in zakat payment should be improved, especially in mall zakat payment. For the management and distribution of zakat optimally, its required zakat institution professionally, trustworthy, and transparently. At Yogyakarta, the management of zakat has been managed by BAZNAS Yogyakarta city. It has tried hardly become a zakat institution professionally, trustworthy and transparently. This research aimed for testing a partial and simultaneous the influence of trust, regulation and BAZNAS product on muzakki’s interest in zakat payment at BAZNAS Yogyakarta. The amount of respondents are 100 respondents. Besides that, it also analyzes the management of zakat in BAZNAS. This type of research was a field research. The data used in this research was primary and secondary data. The sampling technique used was probability sampling. The data collection method used was spreading the questionnaires, interviews and documentation. Data analysis technique that used was validity test, reliability test, classic assumption test and multiple regression analysis. The results of this research that processed by using SPSS version 17.0 for Windows, with a test model F showed a significant models and the value of F value is 14,601 while the value of F table is 2.463 (F value > F table ), it means the independent variable (trust, regulation and BAZNAS product) were affected the muzakki’s interest simultaneously in zakat payment at BAZNAS Yogyakarta. While the results of the partial test (T test) showed that the trust variable (t count > t table = 3.223 > 1,984) and regulation variable (t count > t table = 2.190 > 1,984) have a significant affect. But the product BAZNAS variable (t count < t table = 1.558 < 1984) not a significant affect on the muzakki’s interest in zakat payment at BAZNAS Yogyakarta city. Meanwhile, the management of zakat in BAZNAS has meets the standards of existing management.